Recent Developments in Asymmetric Hydrogenation and Transfer Hydrogenation of Ketones and Imines through Dynamic Kinetic Resolution - Echeverria, Pierre-Georges; Ayad, Tahar; Phansavath, Phannarath; Ratovelomanana-Vidal, Virginie (Synthesis, 2016)
The transition-metal-catalyzed asymmetric transfer hydrogenation (ATH) and asymmetric hydrogenation (AH) of α- and β-substituted ketone or imine derivatives are efficient methods for accessing chiral alcohols or amines bearing up to three stereogenic centers through a dynamic kinetic resolution (DKR) process. This review provides a summary of recent work in this field, focusing on the development of new catalytic systems and on the extension of these asymmetric reductions to new classes of substrates.1 Introduction2 Asymmetric Hydrogenation via Dynamic Kinetic Resolution2.1 α-Substituted Ketones2.2. α-Substituted β-Keto Esters and Amides2.3 α-Substituted β-Keto Phosphonates and Sulfones2.4 α,α′-Disubstituted Cyclic Ketones2.5 α,β-Disubstituted Cyclic Ketones2.6 Imine Derivatives3 Asymmetric Transfer Hydrogenation via Dynamic Kinetic Resolution3.1 α-Substituted β-Diketones and Ketones3.2 α-Substituted β-Keto Esters, Amides and Phosphonates3.3 β-Substituted α-Keto Esters and Phosphonates3.4 β-Substituted γ-Keto Esters3.5 β-Alkoxy Ketones3.6 Imine Derivatives4 Conclusion
Keywords: asymmetric hydrogenation; asymmetric transfer hydrogenation; dynamic kinetic resolution; chiral alcohols; chiral amines; stereoselectivity; ketones; imines